Tratamento tardio de luxação extrusiva por meio de reimplante intencional - Santos, Eluma Alves dos [UNESP] (2016)
Some dental trauma situations may require different techniques employed in the routine professional. Knowing the repair process in these cases is of great importance for the correct indication. The aim of this study was to report a case of extrusive dislocation treated by intentional replantation. The Y.F. patient, 16 years old, female, attended the Integrated Clinic Araçatuba Dental School for treatment of trauma in maxillary anterior teeth, six days after the incident. On examination it was found that the elements 21 and 22 had to extruded 4 mm from the side, and heightened mobility and pain to percussion. Radiographically, there was an increase of the periodontal ligament space mainly in the periapical region. As the manual repositioning was not opted for the intentional reimplantation followed endodontic treatment of 21 and 22. It carried out the extraction of the teeth, followed by curettage and thorough irrigation with saline for removal of the clot, followed by reimplantation of the tooth. A containment with orthodontic wire was maintained for 14 days, when it started endodontic treatment. Calcium hydroxide dressing changes were performed every two weeks and for 30 days following the final filling. The patient was followed up for 13 months where we observed the aesthetic and functional rehabilitation of the teeth. It was concluded that the knowledge and multidisciplinary approaches are essential for the treatment of cases of trauma dentoalveolar . Intentional reimplantation allowed a conservative approach for the case of late treatment extrusive dislocation, resulting in a clinical success with no reabsorption by the observed period